NIMG-50. DEUTERIUM METABOLIC IMAGING OF THE ALTERNATIVE LENGTHENING OF TELOMERES PATHWAY REPORTS ON TUMOR BURDEN AND PSEUDOPROGRESSION IN LOW-GRADE GLIOMAS. (12th November 2021) - Taglang, Céline; Batsios, Georgios; Mukherjee, Joydeep; Tran, Meryssa; Gillespie, Anne Marie; Hong, Donghyun; Ronen, Sabrina; Luchman, Hema Artee; Pieper, Russell; Viswanath, Pavithra
Abstract: Glioma patient management relies heavily on magnetic resonance imaging (MRI). However, MRI is often inadequate for assessment of tumor burden and pseudoprogression. Non-invasive methods that report on molecular pathways such as telomere maintenance that drive tumor proliferation are needed. Among brain tumors, low-grade astrocytomas (LGAs) use the alternative lengthening of telomeres (ALT) pathway for telomere maintenance. The goal of this study was to identify ALT-linked metabolic alterations that can be exploited for non-invasive magnetic resonance spectroscopy (MRS)-based imaging of LGAs. We examined the patient-derived BT257 model and compared neurospheres that are ALT-dependent (BT257 ALT+) with those in which the ALT pathway has been silenced (BT257 ALT-). Our studies suggest that expression and activity of the rate-limiting glycolytic enzyme phosphofructokinase-1 are significantly higher in BT257 ALT+ neurospheres relative to ALT-, an effect that is associated with elevated glucose flux to lactate. Studies indicate that poly(ADP-ribose) polymerase inhibitors such as niraparib selectively induce telomeric fusion and cell death in ALT-dependent cells. We find that the telomeric fusion-mediated cytotoxicity of niraparib is associated with significantly reduced glycolytic flux in BT257 ALT+ neurospheres. We then examined whether 2 H-MRS using [6, 6'- 2 H]-glucose, which is a clinically translatable method of imaging glycolytic flux, can be used to monitor the ALT pathway in vivo . [6, 6'- 2 H]-glucose flux to lactate is elevated in tumor relative to normal brain in mice bearing orthotopic BT257 tumors. Importantly, following treatment of BT257 tumor-bearing mice with niraparib, lactate production from [6, 6'- 2 H]-glucose is significantly reduced at early timepoints when alterations in tumor volume cannot be observed by MRI, pointing to the ability of [6, 6'- 2 H]-glucose to report on pseudoprogression in vivo . Collectively, our studies mechanistically link the ALT pathway with elevated glycolytic flux via phosphofructokinase-1 and identify deuterium metabolic imaging as a novel, non-invasive method of imaging tumor burden and treatment response in LGAs in vivo .